Perancangan Model Matematis Untuk Penentuan Jumlah Produksi di PT. XZY - Dian Eko Hari Purnomo (Universitas Sarjanawiyata Tamansiswa, 2017)
Determining the amount of production in an industry is a very important thing before starting the production process. Therefore we need a mathematical model that can help industry players in performing production planning. Mathematical model is a formula that helps industry players in PT. XYZ in solving semi-structured problems in the form of production planning. Many techniques are used to create a mathematical model, one of them with Fuzzy Logic. Fuzzy logic is one of the problem solving techniques where membership degrees are usually represented by values between 0 and 1, so they can be more balanced. One of the fuzzy methods that can be used in solving the problem is the Fuzzy Tsukamoto Method which applies weighted average to calculate the amount of production at PT. XYZ as the end result. The mathematical model of determining the amount of production using the Fuzzy Tsukamoto Method is able to produce a more optimal and balanced quantity of production compared to the calculation without using the method.